2015
DOI: 10.1109/tasc.2014.2374873
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hard X-ray and Gamma-ray Detector With Transition Edge Sensor for Nuclear Materials Analysis

Abstract: We have designed and fabricated a hard X-ray and gamma-ray TES spectrometer for nuclear materials analysis. A superconducting tin (Sn) absorber is coupled to the TES film by using a gold (Au) bump post to improve the thermal contact between the absorber and the TES. To obtain a sufficient detection efficiency at the high energy photons near 100 keV, an 8-pixel array of TES microcalorimeters were developed. In this new device, the epoxy glue which is used to connect the absorber and the gold bump post was well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The time constant of slow decay component improved from 24 ms of the epoxy post TES to less than 5 ms of the gold bump post TES. Although the origin of these two time components in the decay curve is still not clearly understood, we consider that the strong thermal coupling between the Ir/Au film and the Sn absorber, which is brought by the high thermal conductivity of the gold bump post, may suppress the decay time constant of the slow decay component [7], [8].…”
Section: Performance Of Gamma-ray Detectionmentioning
confidence: 96%
“…The time constant of slow decay component improved from 24 ms of the epoxy post TES to less than 5 ms of the gold bump post TES. Although the origin of these two time components in the decay curve is still not clearly understood, we consider that the strong thermal coupling between the Ir/Au film and the Sn absorber, which is brought by the high thermal conductivity of the gold bump post, may suppress the decay time constant of the slow decay component [7], [8].…”
Section: Performance Of Gamma-ray Detectionmentioning
confidence: 96%
“…γ-Radiation detection and monitoring systems are important in applications in medical research and therapy, emergency response, national security, nondestructive inspection, nuclear facilities, and space exploration. A number of γ ray detectors have been introduced, which include high purity germanium (HPGe) detector, superconducting transition edge sensor microcalorimeter, scintillation γ ray detector, photoelectric radiation detector, and others. Winkler et al reported a 256-pixel microcalorimeter array for high-resolution spectroscopy of mixed actinide materials, demonstrating an average pixel resolution of 55 eV and full-width at half-maximum of 100 keV . Cooper et al designed a planar high-purity Ge crystal with a reduced-capacitance strip electrode geometry, resulting in both high event throughput and high energy resolution at very high count rates .…”
mentioning
confidence: 99%